Importance of strategic intelligence for national defense (Legal journal - Research in Legal and Social Sciences, 2018)
The fundamental role of strategic intelligence for national defense, can be comprehended by the explanation of how decision-making process takes place at a strategical level of a State, and its influence on the execution. For this purpose, it is convenient to describethe characteristics of defense policy that are considered to be efficient; a brief summary of the design and instrumentation process, and the close relation among foreing policy, economic policy and defense policy of a country. Finally, this essay includes a concise analysis ofcertain common aspects of leader States in defense policy and the way these articulate their actions with the strategic intelligence system.
Keywords: national defense; strategic intelligence; foreign policy; decision-making; interest